EGFR Signaling Regulates Maspin/SerpinB5 Phosphorylation and Nuclear Localization in Mammary Epithelial Cells. - Mariana Tamazato Longhi; Magna Magalhães; Jeffrey Reina; Vanessa Morais Freitas; Nathalie Cella (PLoS ONE, 2016)
Maspin (SerpinB5) is a non-inhibitory serpin (serine protease inhibitor) with very diverse biological activities including regulation of cell adhesion, migration, death, control of gene expression and oxidative stress response. Initially described as a tumor and metastasis suppressor, clinical data brought controversies to the field, as some studies reported no correlation between SerpinB5 expression and prognosis value. These data underscore the importance of understanding SerpinB5 function in a normal physiological context and the molecular mechanism involved. Several SerpinB5 phosphoforms have been detected in different cell lines, but the signaling pathways involved and the biological significance of this post-translational modification in vivo remains to be explored. In this study we investigated SerpinB5 expression, subcellular localization and phosphorylation in different stages of the mouse mammary gland development and the signaling pathway involved. Here we show that SerpinB5 is first detected in late pregnancy, reaches its highest levels in lactation and remains at constant levels during post-lactational regression (involution). Using high resolution isoelectric focusing followed but immunoblot, we found at least 8 different phosphoforms of SerpinB5 during lactation, which decreases steadily at the onset of involution. In order to investigate the signaling pathway involved in SerpinB5 phosphorylation, we took advantage of the non-transformed MCF-10A model system, as we have previously observed SerpinB5 phosphorylation in these cells. We detected basal levels of SerpinB5 phosphorylation in serum- and growth factor-starved cells, which is due to amphiregulin autocrine activity on MCF-10A cells. EGF and TGF alpha, two other EGFR ligands, promote important SerpinB5 phosphorylation. Interestingly, EGF treatment is followed by SerpinB5 nuclear accumulation. Altogether, these data indicate that SerpinB5 expression and phosphorylation are developmentally regulated. In vitro analyses indicate that SerpinB5 phosphorylation is regulated by EGFR ligands, but EGF appears to be the only able to induce SerpinB5 nuclear localization.